Three new species of Androdeloscia Leistikow, 1999 (Oniscidea: Philosciidae) from the Brazilian Amazonia - Grangeiro, Daniela Correia; Souza, Leila Aparecida; Christoffersen, Martin Lindsey (Zootaxa, 2021)
Three new species of Androdeloscia Leistikow, 1999 from the Brazilian Amazonian rainforest are described. Androdeloscia bicornuata sp. nov., A. paraleilae sp. nov., and A. micropunctata sp. nov. were distinguished from the 26 other species of the genus mainly based on the shape of male pleopod I endopod. Androdeloscia bicornuata sp. nov. differs from all the species in the genus by the complex morphology of the distal portion of the male pleopod I endopod bearing hyaline lamella and two horn-like tips. Androdeloscia paraleilae sp. nov. is characterized by the male pleopod I endopod with simple distal portion, without hyaline lamella, and apex represented by a curved tip and inner margin serrate proximally; and by the concavity on the lateral margin of the first maxilla (except for the A. leilae that is related to other listed characteristics). Androdeloscia micropunctata sp. nov. differs from the remaining species of the genus by the male pleopod I endopod with simple distal portion, without hyaline lamella, and apex truncate bearing a small acute tip in the outer corner; and 5+5 teeth on the first maxilla. Some characters related to the genus are later discussed.